PERANAN MAJELIS TAKLIM DALAM MENINGKATKAN SIKAP KEAGAMAAN PEKERJA SEKS KOMERSIAL (PSK) DI LOKALISASI TONDO KECAMATAN MANTIKULORE KOTA PALU - Saefuddin Mashuri; Hatta Fakhrurrozi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2014)
This research study about the role of Majlis Taklim Sabilillah Mosque in improving religious attitudes Commercial Sex Workers at Tondo Kiri. Sabilillah Mosque functioned less well in carrying out propaganda Islamiyah through Majlis Taklim, because only enabled for the implementation of the obligatory prayers five times a day and learning the Koran for children. Religious activity is confined to the religious lectures delivered by teachers, clerics and religious leaders held incidental to the moment of commemoration of the Islamic and Ramadan alone, but never followed by the commercial sex workers who lived in the vicinity of the mosque. While other forms of religious activities, such as; religious education, recitation Koran for mothers, monthly taklim, zikir assemblies were never implemented at Sabilillah Mosque. It is no wonder, if the impact is felt by the people around localization Tondo was minimal, even no effect in improving the religious attitude of commercial sex workers who inhabit the majority of the localization region